Перша міська лікарня Харкова: історія у півтора століття - Робак, І.; Демочко, Г.; Ільїн, В. (Краєзнавство, 2016)
Стаття присвячена історії найстарішого муніципального лікувального закладу Харкова. Проаналізовано керівництво ним, фінансування, господарський стан, кадрове забезпечення, науковий потенціал тощо. Зазначено, що лікарня багато років була найпотужнішим закладом та обслуговувала не тільки значну частину містян, а й жителів губернії (області). Також вона була клінічною базою для кафедр медичного інституту (університету), що підіймало її авторитет та робило роботу ще ефективнішою. Аналіз розвитку закладу охоплює весь його історичний шлях у сто сорок два роки. Статья посвящена истории первого муниципального лечебного заведения Харькова. Проанализированы управление ним, финансирование, хозяйтвенное положение, кадровое обеспечение, научный потенциал и т.д. Отмечено, что больница много лет была самым мощным заведением и обслуживала не только значительную часть жителей города, но и жителей губернии (области). Также больница была базой для кафедр медицинского института (университета), что поднимало её авторитет и делало работу еще болем эффективной. Анализ развития учреждения охватывает весь его исторический путь в сто сорок два года. The article deals with the history of Olexandr Hospital (V.I. Lenin 1st Soviet Hospital, the 1st city clinical hospital) – the oldest municipal institution of the city of Kharkiv. The hospital was founded in 1869 with the support of the governor, mayor and sponsors, who contributed considerable funds for hospital construction and for required equipment for the hospital. Since the foundation and during the time of its existence the hospital was a multi-field healthcare institution. The most powerful departments were the following: therapeutic, surgical, obstetricgynecological and neurological: but there were equally important departments: the ear department, urology, traumatology, tuberculosis, otolaryngology, gastroenterology departments, which were opened after the Second World War. At the time of foundation the hospital had one hundred beds, but the growing demand for qualified medical care caused the increase in the number of beds. In the future, there was a steady trend in the increase of hospital beds; its maximum was reached in the second half of the twentieth century, when the hospital had 720 beds. The hospital was not only a healthcare institution, but also a clinical site for the Departments of Kharkiv Medical Institute (University). The following greats of medical science shared their practical experience with the students – I. Zarubin, A. Podriez, I. Kudintsev, Ie. Chernikov, M. Milostanov, O. Mandelshtam, A. Heimano vych, O. Melnykov, V. Hryshchenko, V. Zaitsev, L. Mala. Reform-minded leaders of the medical field broke almost sesquicentennial history of the hospital, which ceased to exist as an independent institution in 2012.